Marketing in Asia-Pacific logistics companies: A discriminant analysis between marketing orientation and performance - Panayides, Photis (My University, 2004)
The marketing literature has emphasised the importance of marketing orientation as a means of achieving organisational objectives. A number of studies that have examined the marketing orientation and business performance relationship have found mixed results culminating in inconclusive evidence. This paper examines the marketing practices and investigates the marketing strategy-business performance relationship across logistics companies in the Asia-Pacific region. The exploratory analysis suggests a positive relationship between market segmentation and performance. Differentiation and market orientation do not seem to be significantly associated with improved performance, although cross-functional customer focus shows a significant relationship. Further discriminant analysis of the significant predictor variables suggests that two variables, viz. market segmentation and positioning, and cross-functional customer focus are useful in differentiating between high and low performers. Managerial and further research implications for this increasingly important industry in the Asia-Pacific region are discussed. © 2004, Emerald Group Publishing Limited
Keywords: Asia-Pacific; Logistics; Marketing orientation; Performance